Corpora, classroom and context: the place of spoken grammar in English language teaching - Timmis, Ivor (2003)
The main research question investigated in this thesis is: In an era when English is increasingly used in international contexts, how relevant are the grammatical findings of native speaker spoken corpora in the ELT classroom? In terms of original research data, the thesis draws, initially, on data from a large-scale quantitative survey into the attitudes of students and teachers to conforming to native speaker norms. The data from this survey shows that a desire to conform to native speaker norms is not restricted to learners with an obvious need to interact with native speakers. The research evidence also indicates that there is some interest among both teachers and students in conforming to native speaker spoken norms, though there is uncertainty about what these norms are, and reservations about whether they should be part of the learner's productive repertoire. The thesis includes a set of materials designed to be consistent both with the results from the attitudinal research and with current methodological insights from second language acquisition research. The thesis describes how these materials were evaluated and piloted, both to elicit further research evidence concerning the attitudes of learners and teachers to native speaker spoken norms, and to assess the potential viability of the materials in the classroom. In the light of the theoretical arguments and research evidence presented, the thesis concludes that it is both possible and potentially desirable to design materials which raise awareness of aspects of native speaker spoken grammar, while respecting that English is no longer the exclusive property of its native speakers. The wider, concluding argument of this thesis is that it is both possible and desirable for the native speaker in contemporary ELT to be an object of reference without being an object of deference.